Strategisnya manajemen insani dalam penyediaan guru yang berkualitas - David Livingstone Araro; Herry Sumual; Fientje J.A. Oentoe; Jeffry Sony Junus Lengkong; Viktory Nicodemus Joufree Rotty (Researchparks Publishing, 2022)
The educational goals to be achieved include all aspects, both faith, personality, intelligence, and skills. Education seeks to create a superior personality marked by progress in all areas of life, whether spiritual, personality, intelligence, or skills, all of which will benefit students, the environment in which they interact, and also for the progress of the nation and state.This research was conducted using a qualitative descriptive approach. Sugiyono explained the characteristics of qualitative research methods as follows: